Environmental impacts of gold mining in Essakane site of Burkina Faso - GÖKYAY, ORHAN (TAYLOR & FRANCIS INC, 2017)
In this study, environmental impacts on air, water, and soil pollution caused by the exploit of Essakane gold mine, which is located in North Eastern part of Burkina Faso were investigated. Analyses on drinking water were made in the laboratory to determine the concentration of essential chemicals used in gold mining. Dust fallouts have been measured to assess the level of air pollution. The results showed that exploiting of gold mine directly or indirectly contributes to air pollution in Essakane district. The use of chemicals such as cyanide (industrial gold mining) and mercury (artisanal gold mining) to obtain the gold from the ore constitutes a potential risk for the ecosystem, the local population's health, and livestock production. The results also showed that there is a significant degradation of natural landscape and topography of the soil by open-pits mining (industrial mine) and holes dug by artisanal miners.
Keywords: artisanal gold miner; cyanide; mercury; environmental impacts; mineral mining; open-pit mining; HEALTH; MINE